THE ABILITY OF STUDENT IN MASTERING SIMPLE PAST TENSE AT POLITEKNIK NEGERI UJUNG PANDANG - Halim Shanty (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
This research covers the ability of the student at Politeknik Negeri Ujung Pandang in mastering simple past tense.  The problem statement of this research is  How is ability of the student at Politeknik Negeri Ujung Pandang in Mastering Simple Past Tense?. This research used descriptive research method.  It isused to describe the ability of the student at Politeknik Negeri Ujung Pandang in mastering simple past tense. The instrument used in this research is test through completing uncompleted short story.  The research is focused on the student at Politeknik Negeri Ujung Pandang.  There are 20 students as sample, which were taken by using random sampling. The collection data is done by asking the students to complete the uncompleted reading story. The students were given forty minutes to complete the story.  In analyzing data, the writer scores the students’ test. Then, the researcher calculating the means score of students. After that, the researcher categorizes the students’ scores. The result of the research shows that the ability of the student at Politeknik Negeri Ujung Pandang in mastering simple past tense is bad. The mean score was 2.9. This implies that the students’ ability should be improved through more intensive material on simple past.